Mencegah Oral Mucositis Akibat Kemoterapi Pada Anak Dengan Terapi - Rokhaidah; Herlina (AKPER Pasar Rebo, 2018)
Oral mucositis in cancer patients is an inflammation of the oral mucosa that’s produced by chemotherapy agents or radiation therapy. The prevalence of mucositis in children is higher than in adults because of faster cell division in children. Treatment with non-pharmacological and pharmacological agents. In the field of care for prevention and treatment of mucositis in children. Non-farmacological treatment that can be used in the treatment of oral mucositis in pediatric patients with cancer is honey. The aim of this study was to determine the treatment in oral care against oral mucositis due to chemotherapy in children. This research was quasy experiment with nonequivalent control group design. This study involved 34 child respondents as samples. The results showed that honey significanly impacted to the incidence of oral mucositis (P value = 0.013, CI 95%). The incident of oral mucositis in experiment group was lower than the control group. So the researchers recommended honey for oral treatment of patients whose undergoing chemoterapy.